PENGARUH FAKTOR SOSIAL EKONOMI ORANGTUA DAN MUTU PENDIDIKAN DALAM MENINGKATKAN PRESTASI SISWA PADA SD ALWASHLIYAH 4/36 BELAWAN - Al Firah; Sri Anita Azizi (Universitas Dharmawangsa, 2023)
The process of achieving student achievement at SD ALWASHLIYAH 4/36 Belawan is strongly influenced by the background and economic conditions of the family, school and community environment, physical condition and the level of student confidence. Teaching and learning facilities at SD AlWashliyah 4/36 Belawan are quite limited, so they have to be used alternately. This greatly affects the quality of school education, teachers, and the results of graduates. This study uses mixed data (quantitative and qualitative). The results of testing the hypothesis of parents' socio-economic factors (X1) obtained -1.026 <1.677, then H0 is accepted and H1 is rejected. So that partially the socio-economic factor variables of parents have a significant negative effect on student achievement at SD ALWASHLIYAH 4/36 Belawan. Parents' socio-economic factors cannot be used as a measure of student achievement, the intelligence possessed by students depends on the diligence in learning and the efforts made by students. Testing the quality of education (X2) obtained 12.534 > 1.677, then H0 is rejected and H1 is accepted. So that partially the variable quality of education has a significant positive effect on student achievement at SD ALWASHLIYAH 4/36 Belawan. The quality of education determines the quality of schools such as the principal, classrooms, the ability of teachers to implement quality education programs, comfort in schools, etc. The results of the F test show that the value of Fcount > Ftable is 78.605 > 3.20. So it was concluded that simultaneously parents' socio-economic factors and the quality of education had a significant effect on student achievement at SD ALWASHLIYAH 4/36 Belawan. Keywords: Parents' Socioeconomic Factors, Quality of Education, Student Achievement.